Educator and its Role in Society (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This article delves into the pivotal role of educators in shaping and influencing society through the lens of education. It explores the impact of educators on individuals, communities, and the broader societal landscape. Through a comprehensive analysis, the article highlights the responsibilities, challenges, and opportunities that educators face in their quest to contribute to positive societal transformation.